Synthesis of Silver Nanoparticles Using Extracts from Different Parts of the Paullinia cupana Kunth Plant: Characterization and In Vitro Antimicrobial Activity - Alan Kelbis Oliveira Lima; Lucas Marcelino dos Santos Souza; Guilherme Fonseca Reis; Alberto Gomes Tavares Junior; Victor Hugo Sousa Araújo; Lucas Carvalho dos Santos; Vitória Regina Pereira da Silva; Marlus Chorilli; Hugo de Campos Braga; Dayane Batista Tada; José Antônio de Aquino Ribeiro; Clenilson Martins Rodrigues; et al. (MDPI AG, 2024)
The green synthesis of silver nanoparticles (AgNPs) can be developed using safe and environmentally friendly routes, can replace potentially toxic chemical methods, and can increase the scale of production. This study aimed to synthesize AgNPs from aqueous extracts of guarana (Paullinia cupana) leaves and flowers, collected in different seasons of the year, as a source of active biomolecules capable of reducing silver ions (Ag+) and promoting the stabilization of colloidal silver (Ag0). The plant aqueous extracts were characterized regarding their metabolic composition by liquid chromatography coupled to high-resolution mass spectrometry (UHPLC-HRMS/MS), phenolic compound content, and antioxidant potential against free radicals. The synthesized AgNPs were characterized by UV/Vis spectrophotometry, dynamic light scattering (DLS), nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM), and scanning electron microscopy coupled to energy-dispersive X-ray spectrometry (EDX). The results demonstrated that the chemical characterization indicated the presence of secondary metabolites of many classes of compounds in the studied aqueous extracts studied, but alkaloids and flavonoids were predominant, which are widely recognized for their antioxidant capabilities. It was possible to notice subtle changes in the properties of the nanostructures depending on parameters such as seasonality and the part of the plant used, with the AgNPs showing surface plasmon resonance bands between 410 and 420 nm using the leaf extract and between 440 and 460 nm when prepared using the flower extract. Overall, the average hydrodynamic diameters of the AgNPs were similar among the samples (61.98 to 101.6 nm). Polydispersity index remained in the range of 0.2 to 0.4, indicating that colloidal stability did not change with storage time. Zeta potential was above −30 mV after one month of analysis, which is adequate for biological applications. TEM images showed AgNPs with diameters between 40.72 to 48.85 nm and particles of different morphologies. EDX indicated silver content by weight between 24.06 and 28.81%. The synthesized AgNPs exhibited antimicrobial efficacy against various pathogenic microorganisms of clinical and environmental interest, with MIC values between 2.12 and 21.25 µg/mL, which is close to those described for MBC values. Therefore, our results revealed the potential use of a native species of plant from Brazilian biodiversity combined with nanotechnology to produce antimicrobial agents.